Fracturing the affordance space: an account of digitalized alienation - Butler, Michael (Frontiers in Psychiatry, 2024)
This paper investigates the lived experience of alienation as a form of mental strife or pathology as it is connected to the digitalization of modern life. To do so, I deploy the concept of affordances from ecological psychology, phenomenology, and embodied cognition. I propose an affordance-based model for understanding digitalized alienation. First, I argue that the lived sense of alienation is best understood as a fracturing of the affordance space, where possibilities for action are lived as disconnected from one another and therefore from one's personal development and search for meaning. Using this model, I show how the process of digitalization can lead to a lived sense of alienation for modern subjects. On this model, digitalization is alienating insofar as it fractures the affordance space into disconnected fields that invite determinate, separate, repeatable tasksswiping, clicking, scrolling, etc. -rather than offering opportunities for the development of new cognitive and bodily skills that are mutually informing and enriching across different affordance fields.